Illustrated manual of injectable fillers a technical guide to the volumetric approach to whole body rejuvenation - Sadick, Neil S.; Carniol, Paul J.; Roy, Deborshi; Wiest, Luitgard (Series in cosmetic and laser therapy, 2011)
Be equipped to prevent and properly treat potential complications of filler usage and provide patients with safe, reliable, and aesthetically pleasing results. The Illustrated Manual of Injectable Fillers clearly presents and evaluates the uses, limitations, and compositions of the growing variety of available fillers involved in face and body rejuvenation.